Aureoboletus projectellus (Fungi, Boletales) – Occurrence data, environmental layers and habitat suitability models for North America and Europe - Banasiak, Łukasz (Data Brief, 2019)
Aureoboletus projectellus is a bolete species native to eastern North America, which has been introduced to Central Europe. Here we present summarized data about occurrence of the fungus in both disjunctive ranges based on (1) de novo georeferencing of herbarium specimens and occurrence reports; (2) information from peer-reviewed articles, mycological forums and websites; (3) personal observations and (4) from queries sent to Forest Districts and National Parks in Poland. Corresponding background data were acquired from public databases and include range of genus Pinus – obligatory mycorrhizal partner of A. projectellus – and WorldClim bioclimatic data. Both datasets were fit for purpose of range modelling, i.e. were represented as spatially compatible equal-area raster grids encompassing temperate forest biom in eastern North America and Europe. Additionally, maps of habitat suitability, reflecting association between occurrence and background data, were obtained using maximum entropy approach implemented in MaxEnt.